Mitochondrial haplogroups, control region polymorphisms and malignant melanoma: a study in middle European Caucasians. - Sabine Ebner (Public Library of Science (PLoS), 2011)
Background Because mitochondria play an essential role in energy metabolism, generation of reactive oxygen species (ROS), and apoptosis, sequence variation in the mitochondrial genome has been postulated to be a contributing factor to the etiology of multifactorial age-related diseases, including cancer. The aim of the present study was to compare the frequencies of mitochondrial DNA (mtDNA) haplogroups as well as control region (CR) polymorphisms of patients with malignant melanoma (n = 351) versus those of healthy controls (n = 1598) in Middle Europe. Methodology and principal findings Using primer extension analysis and DNA sequencing, we identified all nine major European mitochondrial haplogroups and known CR polymorphisms. The frequencies of the major mitochondrial haplogroups did not differ significantly between patients and control subjects, whereas the frequencies of the one another linked CR polymorphisms A16183C, T16189C, C16192T, C16270T and T195C were significantly higher in patients with melanoma compared to the controls. Regarding clinical characteristics of the patient cohort, none of the nine major European haplogroups was associated with either Breslow thickness or distant metastasis. The CR polymorphisms A302CC-insertion and T310C-insertion were significantly associated with mean Breslow thickness, whereas the CR polymorphism T16519C was associated with metastasis. Conclusions and significance Our results suggest that mtDNA variations could be involved in melanoma etiology and pathogenesis, although the functional consequence of CR polymorphisms remains to be elucidated.